Comparative analysis on the requirement, qualification and responsibility of company secretaries in United Kingdom, Malaysia and India / Sharifah Faatihah Syed Mohd Fuzi ... [et al.] - Syed Mohd Fuzi, Sharifah Faatihah; Abdul Halim, Syahrina 'Adliana; Mohamad Khudzari, Julizaerma; Yussoff, Nor Ezrine (Universiti Teknologi MARA, 2019)
The study aims to compare the requirements, qualifications and responsibility of the company secretary in UK, Malaysia and India. The comparative analysis is made based on the provisions in the Companies Act and the Code of Corporate Governance in the three countries. The study found that every public company (whether listed or unlisted) must have at least one company secretary as required by the Companies Act. These requirements are similar in the UK, Malaysia and India, except that in UK only public company are required to have a company secretary. In general, all countries agreed being a member of a professional body is the basic qualification required to become the company secretary. In addition, the responsibilities of the company secretary were not clearly specify in the Companies Act of both UK and Malaysia. In contrast, the Companies Act 2013 of India provides brief explanation on the responsibility of company secretary.